The Philosophy of Legal Education in Contemporary Ukraine: Worldview Basics - ZAROSYLO, Volodymyr O.; ZAROSYLO, Vitalij V.; KOROSTASHIVETS, Julia H.; BORTNYK, Nadiia P.; PARPAN, Ulyana M. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018, 2019)
The relevance of the study is due to the fact that in society, education is perceived as a spiritual substance, which must develop the abilities and natural instincts of man, and at the same time contribute to the growth of the intellectual potential of not only the individual but society and the state as a whole. The purpose of the research is the philosophical approach as a quality of rethinking of legal education in different epochs and its differences, as well as socio-cultural conditionality of legal education in Ukraine. The materials of the paper imply the practical significance for the university teachers of the legal specializations.